2021
DOI: 10.1080/22221751.2021.2002671
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-phage combinations decrease antibiotic resistance in Acinetobacter baumannii via changes in envelope architecture

Abstract: Multidrug-resistant bacterial infections are becoming increasingly common, with only few last-resort antibiotics such as colistin available for clinical therapy. An alternative therapeutic strategy gaining momentum is phage therapy, which has the advantage of not being affected by bacterial resistance to antibiotics. However, a major challenge in phage therapy is the rapid emergence of phage-resistant bacteria. In this work, our main aim was to understand the mechanisms of phage-resistance used by the top prio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 62 publications
(55 reference statements)
5
56
0
Order By: Relevance
“…Similarly, a previous study by Wang et al (2021) demonstrated a decrease in apparent MIC when colistin was used in combination with phage Phab24 against colistin resistant A. baumannii . They have also identified that phage-resistant strains displayed mutations in genes that alter the architecture of the bacterial capsule and the outer membrane using whole genome sequencing (Wang et al, 2021). Another study showed synergistic activity of some antibiotics commonly used in the treatment of urinary tract infection (UTI) with MDR A. baumannii phage cocktails in human urinary infection models (Bartłomiej Grygorcewicz et al,.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similarly, a previous study by Wang et al (2021) demonstrated a decrease in apparent MIC when colistin was used in combination with phage Phab24 against colistin resistant A. baumannii . They have also identified that phage-resistant strains displayed mutations in genes that alter the architecture of the bacterial capsule and the outer membrane using whole genome sequencing (Wang et al, 2021). Another study showed synergistic activity of some antibiotics commonly used in the treatment of urinary tract infection (UTI) with MDR A. baumannii phage cocktails in human urinary infection models (Bartłomiej Grygorcewicz et al,.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, in our study, we observed complete inhibition of a few biofilm producing A. baumannii strains when a phage cocktail BNDM(1,2,3,4,9) was combined with 16 µg/ml colistin. Similarly, a previous study by Wang et al (2021) demonstrated a decrease in apparent MIC when colistin was used in combination with phage Phab24 against colistin resistant A. baumannii . They have also identified that phage-resistant strains displayed mutations in genes that alter the architecture of the bacterial capsule and the outer membrane using whole genome sequencing (Wang et al, 2021).…”
Section: Discussionsupporting
confidence: 53%
“…There is a need to improve the current workflow, from phage discovery to the application of phages, which includes investigating the efficacy of a phage in a simple animal model ( 17 , 18 ). Many studies have reported the use of wax worms ( Galleria mellonella ) as a model to study the efficacy of bacteriophages ( 15 , 19 22 ). However, it requires a skillful operator to inject bacteria and/or phages into individual larvae, which sometimes could result in large variations between batches and thus lead to nonreproducible observations.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, recent data point towards a potential benefit of combination therapy utilizing conventional antimicrobial drugs and phages. Sublethal concentrations of antibiotics were shown to augment phage efficacy [57][58][59], while on the other hand phage application can trigger changes in bacteria that reduce their virulence or even restore their susceptibility against antibiotics [60][61][62][63]. However, unfavorable antagonistic interactions between certain antibiotics and phages have also been described and thus need to be considered [64].…”
Section: Discussionmentioning
confidence: 99%